2011
DOI: 10.4137/cmo.s4867
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-Induced Constipation in Advanced Illness: Safety and Efficacy of Methylnaltrexone Bromide

Abstract: Constipation, one of the major side effects of opiates used in palliative care, can impair patients’ quality of life to a point where it prevents sufficient pain control. Methylnaltrexone is a novel μ-receptor antagonist, which does not pass the blood brain barrier. It is licensed to treat opiate induced constipation for patients with advanced diseases. This review article presents an overview of pharmacology and safety of its application, evidence of its efficacy and economic aspects of its use in clinical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…All these benefits in OIC were observed without any detrimental impact on analgesia or opioid requirement. However, the risk of myocardial infarction seems to be increased with the longterm use of alvimopan [30]. It should be reminded here that alvimopan has yet not been approved for OIC.…”
Section: Pamorasmentioning
confidence: 91%
See 1 more Smart Citation
“…All these benefits in OIC were observed without any detrimental impact on analgesia or opioid requirement. However, the risk of myocardial infarction seems to be increased with the longterm use of alvimopan [30]. It should be reminded here that alvimopan has yet not been approved for OIC.…”
Section: Pamorasmentioning
confidence: 91%
“…Another benefit noticed was the rapid onset of action with among the patients who had laxation within the first 4 h, half having it within 30 min of the drug administration [13]. In patients with creatinine clearance of <30 ml/min, 50% dose reduction has been recommended [30]. Some cases of bowel perforation have been observed, especially in patients with an underlying bowel disease [35].…”
Section: Pamorasmentioning
confidence: 97%
“…It is a common problem (Rhondali, Nguyen et al 2013, Van Lancker, Velghe et al 2014) and has been found to be one of the "top 10" of bothersome symptoms for patient's receiving palliative care (Esper 2010, Potter, Hami et al 2003, Walsh, Donnelly et al 2000. Many symptoms may occur as a consequence from constipation, as abdominal pain, increased weakness (Downing, Kuziemsky et al 2007), decreased appetite, nausea (Clark, Smith et al 2012), haemorrhoids, faecal incontinence (Eoff, Lembo 2008), bloating and vomiting (Bader, Jaroslawski et al 2011). …”
Section: Constipationmentioning
confidence: 99%
“…Opioid receptor antagonists (e.g. Methylnaltrexone) inhibit opioid actions in the opioid receptors on the gastrointestinal tract and it used when reduced response to laxative [34].…”
Section: Pharmacological Managementmentioning
confidence: 99%